Ethical Principles in Medical Error Disclosure: From Harm to Healing in Clinical Practice - Zolkefli, Yusrita (Malaysian Journal of Medical Sciences, 2025)
The disclosure of medical errors constitutes a critical element of patient-centred care, one that is both ethically complex and indispensable. This paper explores how the principles of autonomy, beneficence, non-maleficence, and justice provide an ethical foundation for transparent communication, while also confronting challenges such as paternalism and systemic inequities that disproportionately affect marginalised communities. Institutional frameworks, such as the Communication and Optimal Resolution (CANDOR) process, are presented as mechanisms for advancing accountability, learning, and transparency. The discussion reinforces the need for ethical training, protective policies, psychological support for clinicians, and multidisciplinary collaboration. It further asserts that disclosure is a shared ethical responsibility, one that cultivates trust, promotes fairness, and contributes to the continuous improvement of safer and more equitable healthcare systems.